Erratum: HO, GEORGE WAI-CHUN (2012) Notes on the genera Sinophasma Günther, 1940 and Pachyscia Redtenbacher, 1908 (Phasmatodea: Diapheromeridae: Necrosciinae), with the description of four new species from China. Zootaxa, 3495, 57–72. - Ho, George Wai-Chun (Zootaxa, 2012)
(Erratum)